The English Subtitle of “Pertempoeran Soerabaja 1945” by Aris Production's at Museum 10 Nopember Surabaya - Riesta Deria Supriyabudi (PGRI Provinsi Jawa Timur, 2021)
This project focuses on the process followed in the production of the English subtitles for the movie “Pertempoeran Soerabaja 1945,” with a focus on transcription techniques and translation methods. Subtitles are a meant to provide a translation that allows one who does not understand the original content of the film by rendering it into their own language. Movies are an audio-visual format. They are a form of media that conveys information in order to make viewers aware of that information, and also often to entertain them simultaneously. Advanced by technological support, movies contain frames and sounds that are synchronized; they thus easily attract the viewers’ attention. However, there are differences between languages that create difficulties in finding the best equivalent in the target language (TL) to represent the meaning of the source language (SL). The results of this study of the English subtitles of “Pertempoeran Soerabaja 1945” movie reveal that the procedures applied by the translator involved structural processes, a free translation method, as well as subtraction procedure and adaption method, transposition, and semantic procedures. The History of Surabaya in 1945 subtitled in English been included in this project to further clarify the content under study for both native and non-native speakers.